Recycling of Polycarbonate/Acrylonitrile Butadiene Styrene Blends with Flame Retardant Additives for 3D Printing Filament - Lejalem Haile Zegeye; Desalegn Atalie (Journal of Engineering)
Recycling waste from electrical and electronic equipment (WEEE) for valuable materials is a critical aspect of the circular economy and sustainable waste management. Recycling these solid wastes into value-added products is one method for reducing landfill waste and pollution. The purpose of this research was to investigate the recyclability of plastic wastes of Polycarbonate Acrylonitrile Butadiene Styrene blends with Brominated Flame-Retardant additives (PC-ABS-FR). Two types of plastic wastes, PC-ABS-FR (GL) and PC-ABS-FR (DB), were collected and converted into polymer chips using a mechanical process. To study the effectiveness of waste recyclability, 3D printing filaments were produced through the extrusion process. Chemical elements, functional groups, and thermal and mechanical properties of recycled products were evaluated using EDX, FTIR, DSC, and universal tensile testing equipment, respectively. TGA, cone calorimetry, and melt flow index analyses were also carried out. The results showed that recycled PC- ABS–FR (GL) waste-based filament samples had better thermal and mechanical properties. On the contrary, PC- ABS–FR (DB) waste recyclability was not effective in filament extrusion. The mechanical properties of the 3D printing filaments produced from PC-ABS-FR electronic waste were found to be similar to those observed in commercially available and previously reported filaments. The strength, thermal property, cross-sectional homogeneity, and filament diameter of 1.8 ± 0.03 mm of the 3D printer filament made from PC- ABS–FR (GL) were suitable for 3D printing applications such as children’s toys, dust bins, and flower vases.